ETHNOMATHEMATICS AND DIGITAL TECHNOLOGY INTEGRATION IN PROBABILITY INSTRUCTIONAL DESIGN: DEVELOPMENT AND FEASIBILITY STUDY FOR EIGHTH-GRADE MATHEMATICS - Ayu Rindi Antika; Cecep Kustandi; Khaerudin (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study addresses the weak probabilistic reasoning of Indonesian junior high school students, the most challenging competency within the Data and Uncertainty domain, by developing an ethnomathematics-based instructional design integrated with digital technology. Using a research and development approach guided by the Dick and Carey model combined with Merrill’s First Principles of Instruction, three traditional games containing authentic probabilistic structures Hompimpa, Dadu Koprok, and Congklak were transformed into a hierarchical learning sequence on the NumerasiBudaya e-learning platform. Data were gathered through needs-assessment interviews, expert validation, and a one-group pretest-posttest trial involving 24 eighth-grade students at SMP Labschool Cirendeu. Expert review indicated very high feasibility (97,33%), while the trial revealed a moderate gain in numeracy literacy (N-Gain = 0.399; t(23) = 5.297, p < .001, Cohen’s d = 1.081). These findings suggest that culturally grounded, technology-integrated instructional design can meaningfully support junior high school students’ probabilistic reasoning development.